(untitled) (Medical Forum Monthly, 2024)
Aims and Objectives: This study was designed to evaluate the protective role of melatonin on the morphology of proximal convoluted tubules (PCT) of albino rats made nephrotoxic by a chemotherapeutic drug like streptozotocin (STZ). Study Design: Prospective experimental study. Place and Duration of Study: This study was conducted in the Department of Anatomy, Basic Medical Sciences Institute (BMSI), Jinnah Post graduate Medical Centre (JMPC), Karachi, for 6 weeks from March to April, 2012. Materials and Methods: 60 male albino rats were divided into 4 groups, containing 15 animals each. Group A was treated as control, groups B & C received 37 mg/kg STZ Intraperitoneally (I/P) once at the start of experiment, whereas group C additionally received 10mg/100 ml of melatonin (MEL) 3-days prior to STZ administration, and group D received only MEL at the same dose. Serum glucose was measured weekly. The kidneys were processed for histological examination and periodic Acid Schiff Haematoxylin (PAS-H) stained sections were viewed under the light microscope for detailed morphological examination of the proximal convoluted tubules. Results: The microscopic examination revealed marked epithelial, cytoplasmic and nuclear changes in the P.C.T. of STZ treated group B & a significant reduction in the severity of these changes in MEL treated group C. Serum glucose was significantly increased in both group B and C. Conclusion: The results of the investigation indicated that MEL administration suppressed the progression of renal injury induced by nephrotoxic drugs like STZ. It could not decrease STZ induced hyperglycaemia, but it did prevent the histopathological damage of the P.C.T. So dietary supplementation of MEL could be an easy and inexpensive method of protecting cancer patients from renal damage caused by chemotherapy induced oxidative stress.